(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article delves into the concept of implicit expression within the realm of English linguistics. It examines various linguistic phenomena where implicit meaning is conveyed through language structures and usage. The study aims to elucidate the mechanisms behind implicit expression and its significance in communication and language comprehension.